Physicomechanical, water absorption and thermal properties and morphology of Paederia foetida fiber–Al2O3 powder hybrid‐reinforced epoxy composites - Herlina Sari, Nasmi; Suteja, Suteja; Pruncu, Catalin Iulian; Setyawan, Indra; Ahmad Ilyas, Rushdan; Lamberti, Luciano (John Wiley and Sons, 2024)
Hybridization of natural fibers with ceramic materials for reinforcing composites allows the optimization of the properties of these materials. For this reason, the present study aims to investigate physical, mechanical, water absorption, swelling and thermal properties as well as morphological characteristics of a hybrid Paederia foetida fibers–alumina powder (PFs–Al2O3)-reinforced epoxy composite. Epoxy resin served as the matrix, while PFs and Al2O3 were employed as reinforcement. Five types of composites were fabricated using the hot-pressing technique. The corresponding ratios of PFs:Al2O3 volume fractions (%) considered here were 0:40 (SFA), 10:30 (SFB), 20:20 (SFC), 30:10 (SFD) and 40:0 (SFE). The results reveal that the density of the hybrid PFs–Al2O3 composites decreased for increasing volume fractions of PFs: from 2.173 g cm−3 of SFA to 1.042 g cm−3 of SFE. The highest values of tensile strength (i.e. 49.085 MPa), tensile elastic modulus (i.e. 1.431 GPa) and impact strength (24 kJ m−2) were obtained for the SFD composite material with 30% volume fraction of PFs and 10% volume fraction of Al2O3: this happened because interface bonds between PFs, Al2O3 and epoxy phases achieved their optimal configuration. Overall, mechanical properties of the hybrid PFs–Al2O3-reinforced epoxy composites were superior to those of composites reinforced only by PF fibers or only by Al2O3. Water absorption and swellability reached their maximum values at the steady state occurring after tested samples remained immersed in water for 820 h. The SFE composite reinforced only by PFs presented the highest water absorption and swelling (i.e. 6.034% and 5.81%, respectively) while for all other hybrid composites (SFD, SFC and SFB) these two quantities remained below 5%. Density and volume fraction of voids of hybrid PFs–Al2O3-reinforced composites were consistent with the corresponding properties of the composites reinforced only by Al2O3 or PFs. SFD was also the most thermally stable material. Scanning electron microscopy observations of fractured surfaces indicated that the microstructure of the PFs–Al2O3-reinforced epoxy composites presents several voids, fiber pullouts and transverse fibers, which together optimize the mechanical response of the composite material. Remarkably, the SFD composite material was highly competitive with the most recently developed hybrid composites employing natural reinforcements. © 2024 Society of Industrial Chemistry. © 2024 Society of Industrial Chemistry.